Medicinal Value of Mushroom: A Deeper Insight - Gupta, Krishna; Tejaswini, Masne; Umekar, Milind J. (Current Indian Science, 2024)
Fungi are widely acknowledged as one of the most diverse and ecologically significant organisms with substantial economic importance on Earth. Edible and medicinal mushrooms have been recognized by human societies since ancient times, serving not only as valuable sources of nourishment but also as medicinal agents. The primary objective of this study is to explore the fruiting bodies of edible mushrooms and assess their capacity to serve as reservoirs of bioactive metabolites with pharmaceutical potential. The extensive analysis conducted aimed to elucidate the significant potential of these medicinal mushrooms, comparable to that of plants, in producing valuable bioactive compounds, thereby positioning them as abundant reservoirs for pharmaceutical compounds.Fungi produce many different bioactive compounds of different molecular weights, including lectins, lipids, peptidoglycans, phenols, polyketides, polysaccharides, proteins, polysaccharide-protein/peptide complexes, ribosomal and non-ribosomal peptides, steroids, terpenoids, and others. These compounds have more than 130 different therapeutic properties, such as analgesic, antimicrobial, antifungal, anti-inflammatory, anti-plaque, antiviral, cytotoxic, hepatoprotective, cholesterol-lowering, blood-sugar-lowering, blood-pressure-lowering, immune system, response system modulation, immune suppression, cell growth stimulation or regeneration, and more. Several bioactive polysaccharides or polysaccharide-protein complexes identified in these medicinal mushrooms seem to augment both innate and cell-mediated immune responses. Furthermore, these compounds display anti-tumor properties in both animal models and humans.
Keywords: Fungi